Scenarios of seed purchase versus free sourcing and motivations for seed source choice. The case of sweetpotato in Uganda - Namirumi, J.; Kilwinger, F.; Ynte van, D.; Rajendran, S. (2024)
Farmers traditionally source sweetpotato planting materials from various outlets. Their decisions on sourcing and purchasing of sweetpotato planting materials are influenced by a complex interplay of factors that are important in the designing of effective seed system interventions. Nonetheless, most studies primarily focus on the adoption of improved seeds and use of formal seed systems. They often emphasize correlations and thereby overlook the broader goals and motivations driving farmers' choices. This study applied economic psychology principles through a means-end chain (MEC) analysis to investigate attributes farmers' associate with different sweetpotato seed sources, the perceived benefits of these attributes, and the personal values driving their decision-making processes. Data used was data collected using a combination of scenario elicitation, attribute elicitation, laddering interviews, and analyzed using descriptive and MEC analyses. Results reveal that compared to farmers who freely source sweetpotato seed, farmers who purchase sweetpotato seed are more involved in farmer groups and training programs. They source information from formal sources like research institutes unlike their counterparts who rely more on community networks and publicly accessible information. While introduction of new varieties is a common circumstance for purchasing seed, financial constraints lead many farmers to rely on free sources within their communities. The Hierarchical Value Map (HVM) reveals that farmers’ motivations for seed source choice are shaped by both immediate agricultural objectives and long-term aspirations for financial security, health and community cohesion. Farmers prioritize attributes such as “clean seed”, “vigorous vines”, and “timely delivery” linking these to immediate goals like achieving high yields, reducing costs and expanding farms. Consequently, contributing to economic benefits like increased income and financial stability and leading to essential outcomes such as health, food security and nutrition as well as strong social ties fostered by social practices like vine sharing. The sweetpotato seed business can therefore thrive by addressing core needs including high quality, accessibility and socially supportive seed systems delivering not only economic returns but also contributing to household nutrition, health and community resilience.